Усан уусмал дахь кластер бүтцийг судлах төхөөрөмжийг автоматжуулах нь - Ш, Мөнхжаргал; Ө, Эсболд (Scientific transaction of the National University of Mongolia. Physics, 2022)
Has been developed and constructed the experimental automatic equipment for investigation of optical inhomogeneous structures in liquid water.